2018
DOI: 10.1155/2018/8545347
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Extracellular Vesicles: General Methodologies and Latest Trends

Abstract: Background Extracellular vesicles (EVs) play an essential role in the communication between cells and transport of diagnostically significant molecules. A wide diversity of approaches utilizing different biochemical properties of EVs and a lack of accepted protocols make data interpretation very challenging. Scope of Review This review consolidates the data on the classical and state-of-the-art methods for isolation of EVs, including exosomes, highlighting the advantages and disadvantages of each method. Vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
834
1
15

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 854 publications
(926 citation statements)
references
References 150 publications
12
834
1
15
Order By: Relevance
“…In addition, EV maintain cell survival, and they also stimulate protein tyrosine phosphorylation and intracellular calcium increase as signaling events associated to sperm capacitation, also maintain cell survival. EV isolated from oviductal fluid obtained from the isthmus and ampulla regions show diameters of 30 to 500 nm, expressing the specific EV markers CD81 and HSP70, as similarly reported by others . The co‐incubation of spermatozoa with membrane fluorescent EV revealed that their incorporation by the cells takes place in a few minutes, reaching a maximum after 2 hours, becoming 62% sperm stained with different patterns.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, EV maintain cell survival, and they also stimulate protein tyrosine phosphorylation and intracellular calcium increase as signaling events associated to sperm capacitation, also maintain cell survival. EV isolated from oviductal fluid obtained from the isthmus and ampulla regions show diameters of 30 to 500 nm, expressing the specific EV markers CD81 and HSP70, as similarly reported by others . The co‐incubation of spermatozoa with membrane fluorescent EV revealed that their incorporation by the cells takes place in a few minutes, reaching a maximum after 2 hours, becoming 62% sperm stained with different patterns.…”
Section: Discussionsupporting
confidence: 83%
“…EV from the ampulla showed 3‐ to 4‐fold higher total protein concentration than that obtained for the isthmus (data not shown). Western blot analysis (Figure D) revealed that the isolated EV from oviductal fluid were positive for CD81 and heat shock protein 70 (HSP70), two well characterized EV protein markers …”
Section: Resultsmentioning
confidence: 99%
“…Among the many methods applied in different fluids and species (reviewed by Konoshenko, Lekchnov, Vlassov, & Laktionov, ) to isolate EVs (microvesicles and/or exosomes), immunoaffinity precipitation and capture is the method most often commercially offered (Exo‐Quick‐TC; System Biosciences) as being easy to perform and quick (Bai et al, ). However, due to the low density and small size of the exosomes, purity is low‐to‐poor and demands further screening of other exosome surface markers, such as CD44 for example (Alvarez‐Rodriguez, Ljunggren, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Another important challenge to the future use of exosomes in therapy is about optimization isolation and purification methods to produce exosomes with high quality and quantity, as well as desirable physicochemical features. The isolation methods can influence significantly on exosome properties including their density, shape, size, surface proteins, biochemical composition, and so on …”
Section: Therapeutic Role Of Exosomes In Cancermentioning
confidence: 99%